Comparison of Account Officer Performance with Equivalent High School Education Background and Education More than High School at PT. Permodalan Nasional Madani Cabang Jember - Ucok Febri Agustinus; A. Dewantoro Marsono (Formosa Journal of Sustainable Research, 2023)
This study aims to analyze the comparison of account officers' performance based on their educational background, both those who have a high school background and an educational background more than high school, at PT. Permodalan Nasional Madani Cabang Jember. This type of research uses a quantitative type of research. This research uses quantitative research methods, where the research will be analyzed using descriptive statistics using multiple linear regression formulas. In collecting data this study used questionnaires. A total of 147 superiors Account Officer PT. Permodalan Nasional Madani Cabang Jember is used as a population, and used as a sample of 100 superior account officers. This research shows that education level affects account officer performance positively